Singapore - An e-government delight and managing the same for India - Gulati, Archana G. (2006)
It has been amply demonstrated by e-government success stories, such as Singapore, that the effective implementation of e-government apart from improving service delivery, and civil servant's performance, also increases transparency and reduces administrative corruption. With greater public access to government rules, procedures and performance data, transparency is enhanced. Implementation of e-government makes it possible to monitor government officer's decisions online, brings about automation of procedures, reduces the discretionary powers of public officials and eliminates intermediaries, thus lowering the scope for corruption. - Reproduced.
Keywords: E governance - Singapore; E governance